Stress reduction strategies in breast cancer: review of pharmacologic and non-pharmacologic based strategies - Gosain, Rohit (Semin Immunopathol, 2020)
Breast cancer is the most common cancer diagnosed in women. It is associated with multiple symptoms in both patients and caregivers, such as stress, anxiety, depression, sleep disturbance, and fatigue. Stress appears to promote cancer progression via activation of the sympathetic nervous system releasing epinephrine and norepinephrine as well as activation of hypothalamic-pituitary-adrenal axis releasing cortisol. These stress hormones have been shown to promote the proliferation of cancer cells. This review focuses on stress-reducing strategies which may decrease cancer progression by abrogating these pathways, with a main focus on the β-adrenergic signaling pathway. Patients utilize both non-pharmacologic and pharmacologic strategies to reduce stress. Non-pharmacologic stress-reduction strategies include complementary and alternative medicine techniques, such as meditation, yoga, acupuncture, exercise, use of natural products, support groups and psychology counseling, herbal compounds, and multivitamins. Pharmacologic strategies include abrogating the β2-adrenergic receptor signaling pathway to antagonize epinephrine and norepinephrine action on tumor and immune cells. β-Blocker drugs may play a role in weakening the pro-migratory and pro-metastatic effects induced by stress hormones in cancer and strengthening the anti-tumor immune response. Preclinical models have shown that non-selective β1/2-blocker use is associated with a decrease in tumor growth and metastases and clinical studies have suggested their positive impact on decreasing breast cancer recurrence and mortality. Thus, non-pharmacological approaches, along with pharmacological therapies part of clinical trials are available to cancer patients to reduce stress, and have promise to break the cycle of cancer and stress.